Reaching peak emissions - Jackson, Robert B.; Canadell, Josep G.; Le Quéré, Corinne; Andrew, Robbie M.; Korsbakken, Jan Ivar; Peters, Glen P.; Nakicenovic, Nebojsa (Nature climate change, 2016)
Rapid growth in global CO 2 emissions from fossil fuels and industry ceased in the past two years, despite continued economic growth. Decreased coal use in China was largely responsible, coupled with slower global growth in petroleum and faster growth in renewables.